Endogenous exit bias in training programs for unemployed workers - Jochen Kluve; Ulf Rinne; Arne Uhlendorff; Zhong Zhao (Institute for the Study of Labor (IZA), 2012)
This paper assesses the importance of reverse causality when evaluating the impact of training duration for unemployed workers. We use planned duration as an instrumental variable for actual duration. Our results suggest that the potential endogeneity of exits seems to be only relevant in the lower and upper part of the treatment duration distribution.
urn:nbn:de:101:1-201301213276
Keywords: C21; C26; J67; 330; treatment duration; local average treatment effect; dropouts; Arbeitslosigkeit; Weiterbildung; Dauer; Abbrecher; Schätzung; Deutschland